10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Parents of children with Special Educational Needs and Disabilities face challenges on top of everyday parenting, placing them at higher risk of mental health difficulties. However, this could be alleviated by appropriate and timely targeted mental health services. This study examined the experiences of mental health and mental health services in a community sample of parents living in and around York, England. Qualitative data from 66 survey respondents (89.4% female) and 12 interviewees (67% female) were thematically analysed. Results indicated parents experienced numerous challenges related to navigating complexity in their day-to-day lives and in accessing support for their children. Systemic limitations in service accessibility were identified, with participants relying on informal networks and charitable organisations for support due to insufficient or inappropriate formal provision. For some, services were experienced as ineffective or harmful. The absence of appropriate external support for children placed a substantial burden on parents, contributing to psychological distress, isolation, and parents neglecting their own needs to provide for their children. Participants called for more integrated, strengths-based, and family-centred approaches, particularly flexible parallel provision for parents and children. These findings highlight the need for systemic reform to ensure that support services are accessible, joined-up, and responsive to both child and parental needs.